The Whaleness of the Whale: Interspecies Relationality in Moby-Dick and In The Heart of the Sea - Svetlana Seibel (European Journal of American Studies)
Herman Melville’s enigmatic white whale Moby Dick is undoubtedly one of the most famous characters of American literature. His symbolic and allegorical potential, especially as manifested in his “whiteness,” has been given extensive scholarly attention; much less frequently is the personhood of the whale—what I call his whaleness—accorded a sustained discussion. Yet, Melville’s novel raises the question of the personhood of the whale time and time again, and this issue comes into even starker relief when considered as part of the narrative matrix formed by Melville’s Moby-Dick, Owen Chase’s narrative of the sinking of the whaleship Essex in 1820, and Ron Howard’s 2015 feature film In the Heart of the Sea. All these texts are concerned with questions of human-whale relationality and reflect changing debates on human-animal relations by grappling with the whaleness of the whale, each in its own, particular way. This article explores the significance of the theme of human-whale relationality in this narrative matrix, as well as the ways in which its manifestations reflect socio-cultural debates on interspecies relationality.